The Effect of Institutional Ownership and Managerial Ownership on Financial Performance Moderated by Dividend Policy - Langgeng Harum Islami; Sapto Jumono; Agus Munandar; Abdurrahman Abdurrahman (Quantitative Economics and Management Studies, 2022)
This study was conducted to explore the effect of institutional ownership and managerial ownership on financial performance with dividend policy as a moderating variable. The contribution of this research is expected to add information at the theoretical/scientific level of corporate management and also positive managerial implications on the management of profit companies. This study was designed to collect data using a moderate regression analysis data panel with EViews 10 application program. The finding in this study is that a negative effect is not significant of the institutional ownership on the financial performance, variable managerial ownership has a positive effect no significant on the financial performance, and dividend policy as homologizes moderator in the relationship institutional ownership on the financial performance then relationship managerial ownership on the financial performance. The managerial implication of this research for shareholders or potential investors is that appropriate analytical tools are needed to determine the company's financial performance so that decisions are taken precisely because it will affect the return on their investment and for management companies, namely to further increase managerial ownership in the company to improve financial performance.